2021
DOI: 10.1155/2021/8049079
|View full text |Cite
|
Sign up to set email alerts
|

Yixin‐Shu Capsules Ameliorated Ischemia‐Induced Heart Failure by Restoring Trx2 and Inhibiting JNK/p38 Activation

Abstract: Traditional Chinese medicine has shown great safety and efficacy in the treatment of heart failure (HF), whereas the mechanism remains unclear. In this study, the protective effect of Yixin-shu (YXS) capsules, a conventional medicine for various cardiovascular diseases, against myocardial ischemia-induced HF in rats was systematically investigated by RNA-seq technology. HF rats treated with YXS (0.8 or 1.6 g/kg/d, ig) for 6 weeks had significantly decreased brain natriuretic peptide (BNP) and atrial natriureti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…These findings expose mitochondrial dysfunction as a potential therapeutic target in ACR, especially considering promising effects of dietary interventions on mitochondrial bioenergetics. 33,34 Just recently, a dipeptidyl peptidase-4 inhibitor and the inhibitor of the sodium-glucose linked transporter 2 ertugliflozin have been shown to improve mitochondrial oxidative phosphorylation, whether these effects can be transferred to mitochondrial dysfunction in ACR is yet unclear. 35,36 Oxidative stress Impaired mitochondrial respiration in patients suffering from HF has been associated with excessive mitochondrial ROS release and a reduced ATP production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings expose mitochondrial dysfunction as a potential therapeutic target in ACR, especially considering promising effects of dietary interventions on mitochondrial bioenergetics. 33,34 Just recently, a dipeptidyl peptidase-4 inhibitor and the inhibitor of the sodium-glucose linked transporter 2 ertugliflozin have been shown to improve mitochondrial oxidative phosphorylation, whether these effects can be transferred to mitochondrial dysfunction in ACR is yet unclear. 35,36 Oxidative stress Impaired mitochondrial respiration in patients suffering from HF has been associated with excessive mitochondrial ROS release and a reduced ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Our results complement these findings and suggest the translation of alterations in mitochondrial gene regulation in functional alterations. These findings expose mitochondrial dysfunction as a potential therapeutic target in ACR, especially considering promising effects of dietary interventions on mitochondrial bioenergetics 33,34 . Just recently, a dipeptidyl peptidase‐4 inhibitor and the inhibitor of the sodium‐glucose linked transporter 2 ertugliflozin have been shown to improve mitochondrial oxidative phosphorylation, whether these effects can be transferred to mitochondrial dysfunction in ACR is yet unclear 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq technology, which is characterized with high sensitivity, high accuracy, and high coverage, is a suitable method to systematically explore the mechanism of multi-component and multi-target traditional Chinese medicine (TCM) ( Zhang et al, 2020b ; Xiang et al, 2021 ). Applying this technology, Huangbai liniment was identified to activated Nrf2 and its downstream antioxidant genes to facilitate wound healing ( Zhang et al, 2020b ) while the Yixin-Shu capsule was identified to upregulate Trx2 and inhibit JNK/p38 activation to halt heart failure ( Xiang et al, 2021 ). In this study, the potential mechanism of GHI against ischemic stroke was comprehensively and systematically explored by taking advantage of RNA-seq technology.…”
Section: Introductionmentioning
confidence: 99%